2010
DOI: 10.1038/pj.2010.62
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of crosslinked poly(orthosilicate)s based on cyclohexanediol derivatives and their swelling properties

Abstract: Condensations of tetraethyl orthosilicate (TEOS) with cyclohexanediol derivative monomers at moderately high temperatures resulted in the creation of crosslinked poly(orthosilicate)s. The structural and thermal properties of the crosslinked poly(orthosilicate)s polymers were determined by Fourier transform infrared spectroscopy, solid-state 13 C and 29 Si crosspolarization magic angle spinning nuclear magnetic resonance, thermogravimetric analysis and differential scanning calorimetry. The synthesized crosslin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Previously, we synthesized crosslinked poly(orthosilicate)s based on tetraethyl orthosilicate (TEOS) with hydroxyl functional monomers (cyclohexanediols (Karadag et al, 2010), cyclohexanedimethanols and linear aliphatic diols which have fast and high organic solvent absorption properties with oil-derived pollution, reusability and good thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we synthesized crosslinked poly(orthosilicate)s based on tetraethyl orthosilicate (TEOS) with hydroxyl functional monomers (cyclohexanediols (Karadag et al, 2010), cyclohexanedimethanols and linear aliphatic diols which have fast and high organic solvent absorption properties with oil-derived pollution, reusability and good thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The poly(orthosilicate)s were prepared by condensing tetraethyl orthosilicate (TEOS) with hydroxyl functional monomers (based on cyclohexanediols, (Karadag et al, 2010), cyclohexanedimethanols , linear aliphatic diols ) and showed good organic solvent absorption properties.…”
Section: Introductionmentioning
confidence: 99%
“…All of the synthesized polymers were thermally stable and had good, rapid sorption features for organic solvents such as dichloromethane (DCM), tetrahydrofuran (THF), dichloroethane, acetone, and a dry‐cleaning fluid blend. Using the same methodology we previously reported, we have synthesized crosslinked poly(orthosilicate)s with tetraethyl orthosilicate (TEOS) and hydroxyl monomers (based on cyclohexanediol49 or cyclohexanedimethanol50, 51). The obtained polymers are thermally stable and have very fast and efficient organic solvent absorption properties.…”
Section: Introductionmentioning
confidence: 99%